Application of retention basins to reduce the impact of climate change on existing stormwater drainage systems - Taseski, Goce; Nikola Krstovski (Savez inženjera i tehničara Srbije, Beograd, 2024)
We are increasingly witnessing the occurrence of short-term and intense rainfall, which manifests in the flooding of urban areas, causing significant financial damage, and in certain cases it can cause loss of human lives. Therefore, it is becoming more evident that we must immediately confront the challenges of climate change, which primarily require the application of engineering knowledge to reduce their impact, especially in terms of accepting and safely draining stormwater. The aim of this paper is to analyze the application of retenti on basins to reduce peak stormwater runoff by using hydraulic modeling of the existing stormwater drainage system. Specifically, retention basins are becoming increasingly necessary in modern urban planning, where they serve as reservoirs for floodwaters from areas that gravitate towards urban centers.
Keywords: retention basins, stormwater drainage system, hydraulic model